Perlindungan Status Kerja Dan Pengupahan Tenaga Kerja Dalam Situasi Pandemi COVID-19 Berdasarkan Perspektif Pembaharuan Hukum - Kanyaka Prajnaparamitha; Mahendra Ridwanul Ghoni (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2020)
The study aims to determine the protection of work status and remuneration for workers in a co-19 pandemic situation based on the perspective of legal reform. The results showed that in terms of wage protection and protection for workers in the workplace the employer can hold the payment of wages (if the employer is unable to pay wages according to the minimum wage), by first negotiating with workers / laborers or related trade unions / labor unions the suspension. The suspension of payment of the minimum wage by the employer to the worker / laborer does not necessarily eliminate the obligation of the employer to pay the difference in the minimum wage during the suspension period. Then, according to the DKI Jakarta Provincial Manpower, Transmigration and Energy Office Circular Letter Number 14 / SE / 2020 Year 2020 concerning Work From Home Appeals, company leaders are expected to take preventative steps related to the risk of transmitting COVID-19 infections with do homework. Keywords: Work Status, Wages, Labor, Pandemic, COVID-19 Abstrak Penelitian bertujuan untuk mengetahui perlindungan status kerja dan pengupahan tenaga kerja dalam situasi pandemi covid-19 berdasarkan perspektif pembaharuan hukum. Hasil penelitian menunjukan bahwa Dalam hal perlindungan pengupahan dan perlindungan bagi tenaga kerja di tempat kerja pengusaha dapat melakukan penangguhan pembayaran upah (jika pengusaha tidak mampu membayar upah sesuai upah minimum), dengan terlebih dahulu melakukan perundingan dengan pekerja/buruh atau serikat pekerja/serikat buruh terkait penangguhan tersebut.Penangguhan pembayaran upah minimum oleh pengusaha kepada pekerja/buruh tidak serta-merta menghilangkan kewajiban pengusaha untuk membayar selisih upah minimum selama masa penangguhan. Kemudian, Menurut Surat Edaran Dinas Tenaga Kerja, Transmigrasi dan Energi Provinsi DKI Jakarta Nomor 14/SE/2020 Tahun 2020 tentang Himbauan Bekerja di Rumah (Work From Home), para pimpinan perusahaan diharapkan dapat mengambil langkah pencegahan terkait risiko penularan infeksi COVID-19 dengan melakukan pekerjaan di rumah. Kata kunci: Status Kerja, Pengupahan, Tenaga Kerja, Pandemi, COVID-19